Taxing the Disposition Effect: The Impact of Tax Awareness on Investor Behavior. (3rd November 2022) - Bazley, William J.; Moore, Jordan; Murren Vosse, Melina
Abstract: Standard portfolio choice models predict that investors consider the tax implications of trading. However, individuals are disposed toward realizing gains and holding losing investments, behaviors that worsen their performance. We show, in an experimental market, that increasing tax salience reduces the disposition effect between 22% and 47%, leading to higher portfolio balances without increasing total trading activity. Using field data, we find that investors' disposition is sensitive to taxes around tax rate changes when taxes are likely salient. Our analysis demonstrates that increasing tax awareness can affect households' portfolio choices, which suggests policy implications for improving financial decision-making.